Hepatoprotective Activity of Sida Veronicaefolia against RIF+INH induce Hepatotoxicity in Experimental Animals - Pandey, Arti; Jain, Vidhi; Singh Saluja, Manmeet (Journal of Biomedical and Pharmaceutical Research, 2023)
In the present investigation, rats will be given the liver-damaging drug RIF+INH, and the methanol (MESV) extract of the leaves of Sida veronicaefolia will be tested to see how well it protects the rats' livers from damage caused by RIF+INH. The hepatoprotective effects of MESV at a dose of 250 & 500 mg/kg were estimated by using liver function tests and serum profiles. According to the results, the extracts of Sida veronicaefolia at a dose of 250 & 500 mg/kg, not only have a strong hepatoprotective effect by lowering the levels of serum transaminases (SGPT and SGOT), alkaline phosphate, and total bilirubin in the blood, but they also increase the levels of total protein by a lot. The effects of MESV were very similar to those of silymarin, which is given as standard drug treatment.